A Critical Genealogy of Rulership, Abuse, and Institutional Counterbalance in the Islamic Caliphates - Anam, A'azliansyah Farizil; Biçer, Beytullah (Yayasan Pesantren Mahasiswa An-Nur, 2025)
This article challenges conventional debates on Islam and human rights, often focusing on doctrinal compatibility. It argues that a more robust and universal human rights framework must be grounded not in idealized historical traditions, but in a pragmatic acknowledgment of the historical reality of state-sponsored abuse. Employing a critical-historical and genealogical method, this study analyzes primary Islamic sources—including historical chronicles and legal treatises—to reconstruct the political history of governance, dissent, and violence from the pre-Islamic period through the classical caliphates. The findings reveal a profound dissonance between the theoretical ideal of the